The Chromatin Factor HNI9 and ELONGATED HYPOCOTYL5 Maintain ROS Homeostasis under High Nitrogen Provision. Issue 1 (1st March 2019) - Bellegarde, Fanny; Maghiaoui, Amel; Boucherez, Jossia; Krouk, Gabriel; Lejay, Laurence; Bach, Liên; Gojon, Alain; Martin, Antoine
Abstract : Excessive nitrogen supply leads to reactive oxygen species accumulation and requires the function of major transcriptional regulators to maintain physiological balance. Abstract: Reactive oxygen species (ROS) can accumulate in cells at excessive levels, leading to unbalanced redox states and to potential oxidative stress, which can have damaging effects on the molecular components of plant cells. Several environmental conditions have been described as causing an elevation of ROS production in plants. Consequently, activation of detoxification responses is necessary to maintain ROS homeostasis at physiological levels. Misregulation of detoxification systems during oxidative stress can ultimately cause growth retardation and developmental defects. Here, we demonstrate that Arabidopsis ( Arabidopsis thaliana ) plants grown in a high nitrogen (N) environment express a set of genes involved in detoxification of ROS that maintain ROS at physiological levels. We show that the chromatin factor HIGH NITROGEN INSENSITIVE9 (HNI9) is an important mediator of this response and is required for the expression of detoxification genes. Mutation in HNI9 leads to elevated ROS levels and ROS-dependent phenotypic defects under high but not low N provision. In addition, we identify ELONGATED HYPOCOTYL5 as a major transcription factor required for activation of the detoxification program under high N. Our results demonstrate the requirement of a balance between N metabolism and ROS production, and our work establishes major regulators required to control ROS homeostasis under conditions of excess N.